AIDS nos livros didáticos de Biologia: PNLEM 2007, PNLD 2012 e 2015 - Corrêa, Lourdes Maria Campos (2017)
AIDS was considered a worldwide epidemic soon after being first described, in 1981. The beginning was marked by the stigmatization of groups that still remains in the present day, along with prejudices, moralizes and blames of people living with HIV. The textbook, inserted in the school context, can be essential in preventing illness and deconstruction of prejudices, for the promotion of quality of life and happiness. More than provide assorted information about the theme, it must link to the social, historical and cultural context. Thus, the research question was: How AIDS is presented in textbooks of Biology of high school, in Brazil, approved by the National Textbook Program - PNLEM / PNLD, editions of 2007, 2012 and 2015? More specifically, how books dialogue with teenagers regarding this issue? How the manual orients the teachers? Therefore, the present study aimed to investigate aids theme in Biology textbooks approved by the PNLEM/PNLD. The method of content analysis of Bardin was employed, looking for analyze how this content it's inserted and worked in textbooks over all issues that have already occurred (PNLEM 2007, PNLD 2012 and 2015), highlight the possible contributions that the teacher's manual presents on aids to work in the classroom, as well as investigate how books dialogue with the students and teachers about AIDS. As a result, it was found that knowledge in textbooks is related primarily to biological aspects and the arguments are authoritarian and moralizing. The language is distant to young boys and girls, and do not makes them sensitize for the issue. The manuals little add, support and encourage the teacher to propose discussions and deconstruction of prejudices. Along the issues, there were some specific inserts on people living with HIV rights and governmental responsibility, for example, but wasn't added to the debate about AIDS. In general, throughout all editions of PNELM/PNLD, were introduced content updates, but remained little social, cultural and historically contextualized.